Photolithographic-stereolithographic-tandem fabrication of 4D smart scaffolds for improved stem cell cardiomyogenic differentiation. (2nd May 2018) - Miao, Shida; Cui, Haitao; Nowicki, Margaret; Lee, Se-jun; Almeida, José; Zhou, Xuan; Zhu, Wei; Yao, Xiaoliang; Masood, Fahed; Plesniak, Michael W.; Mohiuddin, Muhammad; Zhang, Lijie Grace
Abstract: 4D printing is a highly innovative additive manufacturing process for fabricating smart structures with the ability to transform over time. Significantly different from regular 4D printing techniques, this study focuses on creating novel 4D hierarchical micropatterns using a unique photolithographic-stereolithographic-tandem strategy (PSTS) with smart soybean oil epoxidized acrylate (SOEA) inks for effectively regulating human bone marrow mesenchymal stem cell (hMSC) cardiomyogenic behaviors. The 4D effect refers to autonomous conversion of the surficial-patterned scaffold into a predesigned construct through an external stimulus delivered immediately after printing. Our results show that hMSCs actively grew and were highly aligned along the micropatterns, forming an uninterrupted cellular sheet. The generation of complex patterns was evident by triangular and circular outlines appearing in the scaffolds. This simple, yet efficient, technique was validated by rapid printing of scaffolds with well-defined and consistent micro-surface features. A 4D dynamic shape change transforming a 2-D design into flower-like structures was observed. The printed scaffolds possessed a shape memory effect beyond the 4D features. The advanced 4D dynamic feature may provide seamless integration with damaged tissues or organs, and a proof of concept 4D patch for cardiac regeneration was demonstrated for the first time. The 4D-fabricated cardiac patch showed significant cardiomyogenesis confirmed by immunofluorescence staining and qRT-PCR analysis, indicating its promising potential in future tissue and organ regeneration applications.